The social determinants of national tuberculosis incidence rates in 116 countries: a longitudinal ecological study between 2005-2015 - Fiona A. Költringer; Kristi Sidney Annerstedt; Delia Boccia; Daniel J. Carter; William E. Rudgard (BMC, 2023)
Abstract Background Accelerating declines in tuberculosis (TB) incidence is paramount for achieving global goals set for 2030 by the Sustainable Development Goals and the End TB Strategy. The aim of this study was to identify key country-level social determinants of national TB incidence trends. Methods This longitudinal ecological study used country-level data extracted from online databases from the period 2005-2015. We used multivariable Poisson regression models allowing for distinct within- and between-country effects to estimate associations between national TB incidence rates and 13 social determinants of health. The analysis was stratified by country income status. Results The study sample included 48 low- and lower-middle-income countries (LLMICs) and 68 high- and upper-middle income countries (HUMICs), with a total of 528 and 748 observations between 2005-2015, respectively. National TB incidence rates declined in 108/116 countries between 2005-2015, with an average drop of 12.95% in LLMICs and 14.09% in HUMICs. Between LLMICs, higher Human Development Index (HDI), social protection spending, TB case detection, and TB treatment success were associated with lower TB incidence. Higher prevalence of HIV/AIDS was associated with higher TB incidence. Within LLMICs, increases in HDI over time were associated with lower TB incidence rates. Between HUMICs, higher HDI, health spending, and diabetes prevalence were associated with lower TB incidence, whereas higher prevalence of HIV/AIDS and alcohol-use were associated with higher TB incidence. Within HUMICs, increases in HIV/AIDS and diabetes prevalence over time were associated with higher TB incidence. Conclusions In LLMICs, TB incidence rates remain highest in countries with low human development, social protection spending and TB programme performance, and high rates of HIV/AIDS. Strengthening human development is likely to accelerate declines in TB incidence. In HUMICs, TB incidence rates remain highest in countries with low human development, health spending and diabetes prevalence, and high rates of HIV/AIDS and alcohol use. Here, slowing rising rates of HIV/AIDS and diabetes is likely to accelerate declines in TB incidence.